UPAYA GURU DALAM MENINGKATKAN KREATIVITAS SISWA DALAM EKSTRAKURIKULER SENI TARI DI SMP NEGERI 15 PADANG - Fitria Anggraini; Yuliasma Yuliasma; Zora Iriani (FBS Universitas Negeri Padang, 2018)
AbstractThis article aims to describe the Teacher Efforts in Improving Student Creativity in Extracurricular of Dance Art at SMP Negeri 15 Padang. The type of research was qualitative with descriptive method. The technique of data collection was conducted through literature study, observation, interviews and documentation. Techniques of data analysis were collecting data, describing data, presenting data and drawing conclusions. The results showed that the efforts of teachers in improving the students’ creativity in the Extracurricular of Dance Art at SMP Negeri 15 Padang with the planning of the selection of new dance material which was also supported by the use of media and more varied methods, has been running in accordance with the planned and has achieved the goals as expected. Although, there are still a few obstacles in the execution process of extracurricular activities of dance that is inadequate infrastructure. Based on the researcher observation, the extracurricular activity of dance art is run according to plan, because there has been an increasing students’ creativity. The students who could initially only imitate the dance movement exemplified by the teacher, have been able to develop the dance movement into new movements which are unique and interesting by using the group floor pattern according to their own creativity. Keywords: Improving Creativity, Dance.